The Development of Methodology and Islamic Discourse in Contemporary Western Translations of the Qur’an - Iwanebel, Fejrian Yazdajird; Iffah, Iffah (Institut Agama Islam Negeri (IAIN) Keiri, 2024)
This study examines the translation of the Qur’an in the contemporary Western context, focusing on the post-September 11 tragedy. The translation of the Qur’an at this phase serves as a gateway for understanding Islam and plays a pivotal role in shaping the perception of Islam in Western society. Furthermore, these translations are intertwined with Islamic socio-political discourse. This study's primary objective is to analyze the development of methodological approaches in translating the Qur’an in the contemporary West and explore the production of Islamic discourse within these translations. Using textual and content analysis, this research posits that, firstly, the methodology of Qur’an translation in the contemporary West has witnessed significant advancement in methodological aspects. This can be observed through the transition from literal, interlineal, and polemical translations to more contextual and even reformist translations. Secondly, apart from being influenced by the socio-political landscape of Islam in the West, the translations of the Qur’an also contribute to the creation of Islamic discourse, particularly in shaping the perception of Qur’an translation in the contemporary Western context, which strives for openness, contemporaneity, and the restoration of Islam’s image and the Qur’an’s oral power.